I Do Not Think That Word Means What You Think It Means: A Response to Alcock and Reber’s “Searching for the Impossible: Parapsychology’s Elusive Quest - Westcombe, Andrew (Journal of Scientific Exploration, 2019)
Reber and Alcock’s recent paper in American Psychologist [1] is in many respects typical of the “skeptical” literature on alleged pseudosciences. The following comments will accordingly focus first of all on general features of this topic before addressing more specific features of their paper. This structure is the reverse of the standard approach for scientific papers, but in this instance aids narrative flow. How can we distinguish genuine science from pseudoscience? Pretend for a moment that the vast literature on science versus pseudoscience[2] never existed, and ask yourself how we might clarify this distinction. The first step, of course, would be to clarify the meaning of “pseudoscience”. One possible meaning that we can rule out straight away is that pseudosciences make false claims about the world. They may in fact do so, but so do legitimate sciences. The history of science is the history of discarded hypotheses, so to adopt this interpretation of “pseudoscience” would amount to an assertion that every superseded theory was pseudoscientific, and furthermore prompt the suspicion that much of contemporary science will, in time, likewise be shown to be pseudoscientific. If there is to be a meaningful distinction between science and pseudoscience, it must focus on methods rather than the conclusions that result from those methods. There is of course a literature that attempts to describe and define the scientific method, it too is quite vast and interrelated with the literature on the demarcation problem. [1] Reber, A. S., & Alcock, J. E. (2019, June 13). Searching for the Impossible: Parapsychology’s Elusive Quest. American Psychologist. Advance online publication. http://dx.doi.org/10.1037/amp0000486 [2] Frequently referred to as the “demarcation problem”. My purpose in putting aside this literature is to avoid being drawn into familiar frameworks and disputes, and to undertake this discussion with as few encumbrances as possible.